Analysis of tourism supply of the city of Zagreb and perspectives of its future development - Podovac, Milena; Drpić, Danijel; Milojica, Vedran (Hotel and Tourism Management, 2020)
The specificity of city tourism is reflected in the fact that this form of tourist product enables meeting the needs of tourists with different characteristics, needs and motives by combining existing tourism resources and contents into the city tourism supply. Being the capital of the Republic of Croatia, Zagreb is a significant tourist destination, which has the potential for city tourism development with the aim of improving the competitiveness of this destination in the tourism market. In this paper, the authors performed an analysis of theoretical knowledge about the concept, significance and characteristics of city tourism, an analysis of current tourism supply of the city of Zagreb and of quantitative indicators of tourism development in this city. Based on the analysis of tourism supply, strategic guidelines for improving the development of city tourism in the city of Zagreb have been defined.